2011
DOI: 10.2136/sssaj2010.0127nps
|View full text |Cite
|
Sign up to set email alerts
|

Role of Particle Size and Soil Type in Toxicity of Silver Nanoparticles to Earthworms

Abstract: Silver nanoparticles (NPs) are an emerging contaminant of concern due to their increased use. The earthworm Eisenia fetida was exposed to a range of concentrations of AgNO3 and two polyvinylpyrolidone coated Ag NPs with different particle size distributions. They were exposed in two different soils: a naturally occurring sandy loam and a standardized artificial soil. The AgNO3 significantly reduced E. fetida growth and reproduction at 7.41 ± 0.01 mg kg−1 Ag in the sandy loam but only reproduction was affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
123
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 183 publications
(139 citation statements)
references
References 51 publications
15
123
1
Order By: Relevance
“…Although size influences the toxicity, soil type was found to be more important than particle size [55]. In a sandy loam, the earthworm E. fetida accumulated significantly more Ag from Ag NPs exposure than in artificial soil.…”
Section: Silvermentioning
confidence: 93%
See 4 more Smart Citations
“…Although size influences the toxicity, soil type was found to be more important than particle size [55]. In a sandy loam, the earthworm E. fetida accumulated significantly more Ag from Ag NPs exposure than in artificial soil.…”
Section: Silvermentioning
confidence: 93%
“…The accumulation of Ag seems to be greater in the earthworm E. fetida exposed to the corresponding AgNO 3 salt than from NPs [55,83]. However, extended X-ray absorption fine structure spectroscopy analysis in soil showed that Ag in earthworms exposed to Ag NPs suggests that accumulation was not caused only by the ionic form (i.e., ions dissolved from NPs), but that nondissolved particles contributed to Ag accumulation in the organisms [85].…”
Section: Silvermentioning
confidence: 94%
See 3 more Smart Citations